Forensic Analysis of Mobile Application Security Using the IDFIF v2 Framework - Sutanto, Imam; Setiawan, Abdul Aziz (Universitas Ahmad Dahlan, 2025)
Mobile application security has become an important issue in the midst of increasing cyber attacks, especially on the Android platform. This research aims to analyse the vulnerability of mobile applications using the Integrated Digital Forensics Investigation Framework (IDFIF) version 2 framework with a focus on the Laboratory Process stage. The tool used is Mobile Security Framework (MobSF) for static and dynamic analysis, supported by Genymotion emulator.The results show that the tested application has several vulnerabilities, such as malicious permissions (READ_EXTERNAL_STORAGE and WRITE_EXTERNAL_STORAGE), the use of v1 signature schemes that are vulnerable to Janus attacks, as well as the ability to manipulate the application through bypass debugging. However, no vulnerabilities were found in the SSL Pinning process. These findings provide important insights into security mitigation measures, such as removing malicious permissions, updating certificate mechanisms, and encrypting sensitive data.The application of IDFIF v2 in this investigation demonstrates its effectiveness in systematically detecting and analysing mobile application vulnerabilities, contributing to the development of better security protocols in the future.